2020
DOI: 10.1016/j.jece.2019.103579
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable synthesis of Cs-ABW zeolite nanocrystals from non-reacted mother liquors with excellent catalytic henry reaction performance

Abstract: Nanoscale zeolites are very attractive for advanced applications such as in catalysis, adsorption, supports, sensors and carriers. Green synthesis of these materials is highly appreciated aiming to increase product yield while chemical waste and production cost can be reduced. Here we report high-yield, low-cost and green synthesis of nanosized Cs-ABW zeolite by recycling and using the non-reacted mother liquors waste solutions produced from the hydrothermal Cs-ABW zeolite synthesis. The nanocrystalline Cs-ABW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The direct disposal of the mother liquor will not only lead to the waste of raw materials, but can also cause environmental pollution [12]. Some authors address the reuse and recycling of mother liquor as a raw material for the syntheses of porous materials [13][14][15][16][17][18]. To make synthesis processes more attractive, the principles of green chemistry have been implemented as concepts and actions related to economy, sustainability of resources, and environmental protection [19].…”
Section: Introductionmentioning
confidence: 99%
“…The direct disposal of the mother liquor will not only lead to the waste of raw materials, but can also cause environmental pollution [12]. Some authors address the reuse and recycling of mother liquor as a raw material for the syntheses of porous materials [13][14][15][16][17][18]. To make synthesis processes more attractive, the principles of green chemistry have been implemented as concepts and actions related to economy, sustainability of resources, and environmental protection [19].…”
Section: Introductionmentioning
confidence: 99%
“…The basicity increased to 64.7 (CP-0.3), 69.4 (CP-1.0), and 77.9 μmol g −1 (CP-2.0) when the SBET of the solids increased. Thus, the results show that an addition of TPOAC in the synthesis of hierarchical Cs-pollucite is essential as it enhances the accessible surface area and surface basicity, where the basicity (number of basic sites) of Cs-pollucite, namely (Si-O-Al) − Cs + , is strongly associated with the total accessible surface area of the solids [39]. An attempt to correlate the surface basicity with the amount of TPOAC added and S BET was also made.…”
Section: Synthesis and Characterization Of Hierarchical Cs-pollucitementioning
confidence: 93%
“…Vinaches et al studied the effect of the amount of the mother liquor on the synthesis of MCM-22 and found that the spherical amorphous nanoparticles in the mother liquor accelerated the reaction . Nanocrystalline Cs-ABW zeolite with good catalytic performance for the Henry reaction of benzaldehyde and nitroethane was synthesized by utilizing the mother liquor . Yang et al synthesized pure S-1 from the recycled mother liquor, which not only effectively reduced the cost of S-1 synthesis but also minimized its environmental impact .…”
Section: Introductionmentioning
confidence: 99%